The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1063/5.0092084
|View full text |Cite
|
Sign up to set email alerts
|

Wearable microfluidic patch with integrated capillary valves and pumps for sweat management and multiple biomarker analysis

Abstract: Wearable sweat sensors are essential for providing insight into human physiological health. The currently developed microfluidic sweat sensors have demonstrated the function of collecting and storing sweat. However, they detect more average concentrations of substances based on time periods, which leads to the fact that in situ real-time measurement for multiple biomarkers remains a grand challenge. Here, we propose a wearable epidermal microfluidic patch with integrated microfluidic pumps and micro-valves for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…[ 17 , 18 ]. Therefore, due to the high-density distribution of eccrine sweat glands both in children and adults and the considerable sweat secretion, sweat can be collected non-invasively using a compact epidermal wearable biosensor [ 19 , 20 , 21 ].…”
Section: Sweat Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 17 , 18 ]. Therefore, due to the high-density distribution of eccrine sweat glands both in children and adults and the considerable sweat secretion, sweat can be collected non-invasively using a compact epidermal wearable biosensor [ 19 , 20 , 21 ].…”
Section: Sweat Characteristicsmentioning
confidence: 99%
“…Now, studies have confirmed that perspiration is mainly composed of water (99%); metabolites (such as lactate, glucose, urea, cortisol, hydroxybutyrate, etc.) [ 20 , 25 , 26 , 27 , 28 ]; electrolytes (such as Na + , K + , Cl − , etc.) [ 20 , 29 , 30 ]; trace elements (such as Zn 2+ and Cu 2+ , Fe 3+ , etc.)…”
Section: Sweat Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations